Augmented Reality Navigation on Android: Challenges and Solutions (Journal of Information Technology and Digital World, 2024)
This research focuses on the development of an advanced augmented reality (AR) navigation system, specifically designed to enhance traditional navigation methods and significantly improve overall user satisfaction. By utilizing the latest technological advancements in AR, this system aims to create a more engaging and user-friendly navigational experience. The developed system is based on an Android application that allows users to select their desired routes and navigate to their destination by following virtual direction displayed on their devices. These overlays provide real-time, personalized directions, making it easier for users interact with navigational tools. Unlike traditional map-based navigation, which often requires users to interpret 2D information and imagine how it is related to the real world, this AR system directly shows navigational cues into the real world, making the process more user-friendly. The primary objective of this research is to address the limitations of conventional navigation systems, such as difficulty in understanding map data and getting lost in new places.
Keywords: Augmented Reality; Android; Extended Reality; Navigation System